Occurrence of arsenic in waters and sediments of the Palea Kavala River, NE Macedonia, Northern Greece - Giouri, K.; Vavelidis, M.; Melfos, V. (Bulletin of the Geological Society of Greece, 2013)
However, it can also be added to an aquatic system by anthropogenic activities. The aim of the present study is to determine the total As content in the Palea Kavala river (NE Macedonia, Northern Greece). The correlation between As content and some chemical and physico-chemical parameters of the samples was also examined. Research demonstrated significant As concentrations in the water and the sediments of the river. No correlation was found between As and pH, Fe, Mn in the water samples. Concerning the sediment samples, positive correlation was revealed for As with Fe and Mn content, while negative correlation was revealed between As and pH. This is probably indicative of a higher arsenic mobility in the Palea Kavala river water than in sediments. Since no anthropogenic activities were observed in the river’s catchment area, elevated As concentrations are probably due to the lithology of the broader area and especially the presence of extended ore mineralizations including As-bearing sulphide minerals. However, the research in the study area is in progress since a more detailed evaluation of the local sources of As and mechanisms of As release is required.